2020
DOI: 10.3390/app10041513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Consumption in Different European Cities: The Adaptive Comfort Control Implemented Model (ACCIM) Considering Representative Concentration Pathways (RCP) Scenarios

Abstract: Reports of Intergovernmental Panel on Climate Change have set various greenhouse gas emissions scenarios, through which the evolution of the temperature of the planet can be estimated throughout the 21st century. The reduction of the emissions from the different activities carried out by mankind is crucial to mitigate greenhouse gas emissions. One of the most significant activities is users’ behaviour within buildings, particularly the use of Heating, Ventilation and Air-Conditioning systems. Modifying users’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The effect called meteorological memory, in which both the expectations of the occupants and their psychological adaptation to different temperatures intervene, is taken into account in the adaptive models [47]. Recently, it has been studied, in relation to PE, how this adaptive approach can influence the use of air-conditioning devices by occupants [37,48,49]. This is supported by the use of so-called daily setpoint temperatures, that is, the temperatures that achieve the highest percentage of acceptability to keep the interior at a set temperature within the daily adaptive comfort limits.…”
Section: Adaptive Comfort and Adaptive Energy Consumption Assessments...mentioning
confidence: 99%
“…The effect called meteorological memory, in which both the expectations of the occupants and their psychological adaptation to different temperatures intervene, is taken into account in the adaptive models [47]. Recently, it has been studied, in relation to PE, how this adaptive approach can influence the use of air-conditioning devices by occupants [37,48,49]. This is supported by the use of so-called daily setpoint temperatures, that is, the temperatures that achieve the highest percentage of acceptability to keep the interior at a set temperature within the daily adaptive comfort limits.…”
Section: Adaptive Comfort and Adaptive Energy Consumption Assessments...mentioning
confidence: 99%
“…Lin et al [30] experimentally verified an optimized control strategy for fan-coil units achieving 39.71% energy conservation. Sánchez-García et al [31] found that the adaptive approach in Mediterranean cities can guarantee reductions in cooling consumption (around 50-60%) in contrast with discrete savings for heating (around 20%). Considering the temperature set point strategies, Date et al [32] obtained peak demand reductions of up to 10% and 25% when the conventional night time setback temperature profile was respectively changed with a one hour or two hours ramp with baseboards.…”
Section: Thermal Comfort: Indoor Plant Emitters and Control Strategiesmentioning
confidence: 99%
“…For this reason, this study presents the possibilities of increasing the energy consumption of the buildings analyzed by the CTE under various operational conditions for HVAC systems. Starting from the residential profile established by the CTE, the effect of considering the use periods of heating and cooling systems throughout the year was first analyzed because of the tendencies found in the monthly energy consumptions in several case studies analyzed in Spain [44,45], where there was a heating or cooling energy demand in the months not considered by the CTE's residential profile (e.g., the cooling energy demand in May). Then, the effect of using the cooling system with an indoor setpoint temperature of 25 • C in the time period from 07:00 to 14:59 was analyzed.…”
Section: Introductionmentioning
confidence: 99%